2022
DOI: 10.3389/fgene.2022.951243
|View full text |Cite
|
Sign up to set email alerts
|

Construction, bioinformatics analysis, and validation of competitive endogenous RNA networks in ulcerative colitis

Abstract: Background: Ulcerative colitis (UC) is a common chronic disease of the digestive system. Recently, competitive endogenous RNAs (ceRNAs) have been increasingly used to reveal key mechanisms for the pathogenesis and treatment of UC. However, the role of ceRNA in UC pathogenesis has not been fully clarified. This study aimed to explore the mechanism of the lncRNA-miRNA-mRNA ceRNA network in UC and identify potential biomarkers and therapeutic targets.Materials and Methods: An integrative analysis of mRNA, microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…For instance, Xu et al [ 38 ] performed a comprehensive analysis that revealed four central genes regulated by NF-κB, ultimately constructing an lncRNA-miRNA-transcription factor (NF-κB) interaction network. Another study aimed to demonstrate the high diagnostic accuracy of two mRNAs (CTLA4 and STAT1) within the ceRNA network in UC[ 39 ]. In contrast, we focused on circRNA as a potential clinical diagnostic marker, deviating from conventional approaches, with circRNA possibly offering improved specificity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Xu et al [ 38 ] performed a comprehensive analysis that revealed four central genes regulated by NF-κB, ultimately constructing an lncRNA-miRNA-transcription factor (NF-κB) interaction network. Another study aimed to demonstrate the high diagnostic accuracy of two mRNAs (CTLA4 and STAT1) within the ceRNA network in UC[ 39 ]. In contrast, we focused on circRNA as a potential clinical diagnostic marker, deviating from conventional approaches, with circRNA possibly offering improved specificity.…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the ELN clusters (3, 5, and 6) we implemented this approach to get a more refined examination of the biologically linked process driven by each cluster. We employed several different approaches to perform this analysis, ultimately choosing the Cytoscape network clustering application ClueGO 70,71 , which was employed extensively in recent years for this purpose [72][73][74][75] . The advantage of this network approach is that GO term enrichment is selected based upon networks derived from kappa-score between terms based on similarity of genetic contribution to the particular term.…”
Section: Methodsmentioning
confidence: 99%
“…Bioinformatics analysis has been widely used to search for differentially expression genes (DEGs), miRNA, and functional pathways involved in the development and progression of UC. For example, Wu et al constructed a complete lncRNA-miRNA-mRNA network through bioinformatics to determine the specific immune infiltration characteristics of UC 13 . Moreover, protein–protein interaction (PPI) can provide information about direct and indirect protein interactions for screening hub genes 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%